Analisis Penerapan Laporan Keuangan Berdasarkan SAK EMKM pada UMKM (Studi Kasus pada UMKM Robbani Snack) - Sastri Ayu Lestari; Andi Mulyono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This research aims to find out how financial reports are prepared at Robbani Snack MSMEs, analyze the inhibiting factors that cause Robbani Snack MSMEs not to implement SAK EMKM-based financial reports and provide alternative solutions to the obstacles faced by Robbani Snack MSMEs. This research was conducted at the UMKM Robbani Snack which is located in Mataram village, Kec. Gadingrejo District. Pringsewu. In this research, 3 informants were used, namely 1 informant as the owner and 2 informants as sales assistants and admin. This research uses a qualitative research method with a case study approach. The data sources used are primary data and secondary data. Data collection methods were carried out by means of interviews, documentation and observation. The results of the research show that in preparing financial reports, UMKM Robbani Snack has not implemented SAK EMKM due to a lack of knowledge and understanding of the owner and his assistants about SAK EMKM, educational background, UMKM Robbani Snack feels that it is still a village business that is not yet professional and is not yet able to make financial reports Based on SAK EMKM, there is no socialization from related agencies and there is no supervision from interested parties regarding MSME financial reports, especially from the government, related institutions and regulators. To improve the quality of implementation of SAK EMKM in Robbani Snack MSMEs, it is necessary to select human resources who understand the accounting recording system, conduct training on SAK EMKM and training on the use of accounting software, this is important to do because it can make it easier to prepare financial reports. So there is a need for outreach from relevant agencies regarding accounting, this can help MSME players gain knowledge related to accounting. And there is also a need for supervision from interested parties regarding MSME financial reports, especially from the government, related institutions and regulators.